Splendors of Faith : New Orleans Catholic Churches, 1727-1930 - Nolan, Charles E. (Book collections on Project MUSE., 2010)
"A gumbo of French, Spanish, and American influences, the architecture of New Orleans has always reflected the city's strong Catholic roots. Indeed, St. Louis Cathedral across from Jackson Square stands as perhaps the most widely recognized face of New Orleans. The cathedral, though, is just one of the many stunning churches that beautifully display the Crescent City's long and diverse Catholic heritage. Splendors of Faith showcases thirteen of these historic churches of exceptional architectural and artistic merit, revealing scenic treasures that lie mostly beyond the well-worn tourist paths"--Page 2 of cover